Penerapan Circular Economy dalam Pengelolaan Limbah Di Pondok Pesantren Subulul Huda - Adinda Rizqi Nur Azizah; Fibrianis Puspita Anhar (Niqosiya: Journal of Economics and Business Research, 2025)
This research examines the implementation of the circular economy concept through waste management at the Subulul Huda Kembangsawit Islamic Boarding School. As the number of students increases, this boarding school faces increasingly complex waste management challenges, which reach 150 kg every day. Since 2000, Islamic boarding schools have begun to implement the circular economy concept which was initiated by the caretaker council and Asatid as a solution to the problem of burning waste. This research uses qualitative methods, data is collected through interviews, observation and documentation. The research results show various waste management initiatives through seven main activities that follow the 5R concept (reduce, reuse, recycle, refurbish, and renew) including: managing organic waste into animal feed and fertilizer, managing inorganic waste into various creative products, conditioning waste water through IPAL, using used clothes through a thrifting program, reusing used building wood into furniture, using cloth sanitary napkins for female students, and using refillable liquid washing soap to reduce plastic packaging. Islamic boarding schools optimize circular economy activities through socialization and waste management training for students. This research contributes to the development of a circular economy-based waste management model that can create a clean, healthy, sustainable environment and increase financial independence in Islamic Education Institutions. The findings of this research can be a reference for the government in formulating environmental management policies that are integrated with Islamic values and provide practical guidance for other Islamic educational institutions in developing sustainable environmental management programs.